2020
DOI: 10.1016/j.omtn.2020.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Associations of lncRNA H19 Polymorphisms at MicroRNA Binding Sites with Glioma Susceptibility and Prognosis

Abstract: Glioma is the most common tumor of the central nervous system; variation in susceptibility and prognosis worldwide suggests that there are molecular and genetic differences among individuals. The H19 gene plays a dual role in carcinogenesis. In this study, associations between H19 polymorphisms and susceptibility as well as prognosis in glioma were evaluated. In total, 605 patients with glioma and 1,300 cancer-free subjects were enrolled in the study. Individuals with the rs3741219 A>G allele were less likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…Notably, a significant three-loci interaction model of rs3741219-rs2839698-rs6478974 was identified to increase the risk of epilepsy. Our results were consistent with some previous reports in central nervous system diseases, which found that the G rs217727 A rs2839698 G rs3741219 haplotype carriers were less likely to develop glioma 39 and the 3-loci model of rs2280543-rs217727-rs2839698 conferred the risk of intracranial aneurysm. 40 With regard to the association between H19 polymorphisms and risk ischemic stroke (IS), conflicting results were obtained.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, a significant three-loci interaction model of rs3741219-rs2839698-rs6478974 was identified to increase the risk of epilepsy. Our results were consistent with some previous reports in central nervous system diseases, which found that the G rs217727 A rs2839698 G rs3741219 haplotype carriers were less likely to develop glioma 39 and the 3-loci model of rs2280543-rs217727-rs2839698 conferred the risk of intracranial aneurysm. 40 With regard to the association between H19 polymorphisms and risk ischemic stroke (IS), conflicting results were obtained.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, this region encodes for the antisense transcript HOTS. But so far, there is no evidence for a co-expression of H19 and HOTS in vivo [86]. In HCC, the T allele of H19 rs217727 polymorphism, which is associated with decreased H19 expression, enhanced the survival rate of patients with HCC [101].…”
Section: The Role Of H19 Ex Vivo-human Samplesmentioning
confidence: 99%
“…Nevertheless, it is essential to compare these results with human HCC samples. Most human studies show that H19 is overexpressed in HCC [28,30,66,[86][87][88][89][90][91]. Early investigations indicated an elevation of H19 in human HCC samples [32,[89][90][91].…”
Section: The Role Of H19 Ex Vivo-human Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The “T” allele at H19 rs2839698 was reported to be associated with bladder cancer [ 25 ], renal cell carcinoma [ 34 ], ovarian cancer [ 35 ], hepatoblastoma [ 36 ], hepatoma cell carcinoma [ 37 , 38 ], gastric cancer [ 39 ], colorectal cancer [ 40 , 41 ], and breast cancer [ 42 ]. Meanwhile, H19 rs2839698 was reported not to be associated with oral cancer [ 43 ], lung cancer [ 44 ], cervical cancer [ 45 ], glioma [ 46 ], and neuroblastoma [ 47 , 48 ]. On the contrary, H19 rs217717 was reported to be associated with altered risks of hepatoblastoma [ 36 ], gastric cancer [ 39 ], oral cancer [ 43 ], and lung cancer [ 44 ], while whether the “T” allele is a risk or protective is still controversial [ 26 , 42 , 49 ].…”
Section: Discussionmentioning
confidence: 99%